Clinical Validation of Adjusted Corneal Power in Patients with Previous Myopic Lasik Surgery - Camps, Vicente J. (J Ophthalmol, 2015)
Purpose. To validate clinically a new method for estimating the corneal power (P (c)) using a variable keratometric index (n (kadj)) in eyes with previous laser refractive surgery. Setting. University of Alicante and Medimar International Hospital (Oftalmar), Alicante, (Spain). Design. Retrospective case series. Methods. This retrospective study comprised 62 eyes of 62 patients that had undergone myopic LASIK surgery. An algorithm for the calculation of n (kadj) was used for the estimation of the adjusted keratometric corneal power (P (kadj)). This value was compared with the classical keratometric corneal power (P (k)), the True Net Power (TNP), and the Gaussian corneal power (P (cGauss)). Likewise, P (kadj) was compared with other previously described methods. Results. Differences between P (cGauss) and P (c) values obtained with all methods evaluated were statistically significant (p < 0.01). Differences between P (kadj) and P (cGauss) were in the limit of clinical significance (p < 0.01, loA [−0.33,0.60] D). Differences between P (kadj) and TNP were not statistically and clinically significant (p = 0.319, loA [−0.50,0.44] D). Differences between P (kadj) and previously described methods were statistically significant (p < 0.01), except with P (cHaigisL) (p = 0.09, loA [−0.37,0.29] D). Conclusion. The use of the adjusted keratometric index (n (kadj)) is a valid method to estimate the central corneal power in corneas with previous myopic laser refractive surgery, providing results comparable to P (cHaigisL).